Hepatoprotective and anticlastogenic effects of ethanol extract of Irvingia gabonensis (IG) leaves in sodium arsenite-induced toxicity in male Wistar rats (Nigerian Journal of Physiological Sciences, 2021)
Summary: Consumption of arsenic contaminated water has been associated with diverse health defects such as cancer and skin lesions. Some plants of medicinal value have been reported to show protective effects against toxins. In this study, the effects of ethanol extract of the leaves of Irvingia gabonensis (IG) against sodium arsenite (SA) induced hepatotoxicity and clastogenicity in male Wistar rats was investigated. Eight groups of five rats each were used for the study. They were administered with 250 or 500 mg/kg body weight of IG with or without SA at 2.5 mg/kg body weight. IG extract has a significant (p